Hubungan Efek Samping dengan Kejadian Dropuot Penggunaan Alat Kontrasepsi Bawah Kulit (AKBK) di PMB Erna Wati Kecamatan Lawe Sumur Kabupaten Aceh Tenggara Tahun 2024 - Sonia Novita Sari; Putri Maharani; Imarina Tarigan (Quantum Wellness : Jurnal Ilmu Kesehatan, 2024)
The subcutaneous contraceptive device (AKBK) is an effective and efficient hormonal contraceptive device in the form of a rod that is implanted under the skin, namely the upper arm and the protection period can reach five years. The aim of the research is to study the relationship between side effects and the incidence of dropouts in the use of subcutaneous contraceptives. The research method is a quantitative analytical survey with a cross sectional approach. The population in this study were all family planning acceptors who visited PMB Erna Wati, Lawe Sumur District, Southeast Aceh Regency, both those who used AKBK and those who dropped out, namely 45 acceptors. Chi square data analysis technique. The conclusion of this research is that there is a relationship between side effects and the incidence of dropouts in the use of under-the-skin contraceptives (AKBK). There is a relationship between side effects and the incidence of drop-outs in the use of under-the-skin contraceptives (AKBK) in 2024. It is hoped that this will serve as input for Health Officers to improve the implementation of providing education to mothers regarding use. AKBK